Diphenhydramine inhibits voltage-gated proton channels (Hv1) and induces acidification in leukemic Jurkat T cells- New insights into the pro-apoptotic effects of antihistaminic drugs. Issue 1 (1st January 2018) - Asuaje, Agustín; Martín, Pedro; Enrique, Nicolás; Zegarra, Leandro Agustín Díaz; Smaldini, Paola; Docena, Guillermo; Milesi, Verónica
ABSTRACT: An established characteristic of neoplastic cells is their metabolic reprogramming, known as the Warburg effect, with greater reliance on energetically less efficient pathways (such as glycolysis and pentose phosphate shunt) compared with oxidative phosphorylation. This results in an overproduction of acidic species that must be extruded to maintain intracellular homeostasis. We recently described that blocking the proton currents in leukemic cells mediated by Hv1 ion channels triggers a marked intracellular acidification and apoptosis induction. Moreover, histamine H1-receptor antagonists were found to induce apoptosis in tumoral cells but the mechanism is still unclear. By using Jurkat T cells, we now show how diphenhydramine inhibits Hv1 mediated currents, inducing a drop in intracellular pH and cellular viability. This provides evidence of a new target structure responsible of the known pro-apoptotic action of antihistaminic drugs.